Subiasiana indica gen. nov., sp. nov., a new remarkable representative of Uropodina mites from India (Acari: Mesostigmata: Uropodidae) - Kontschán, Jenő (Zootaxa, 2024)
A new genus, Subiasiana gen. nov. (Mesostigmata: Uropodina: Uropodidae), with Subiasiana indica sp. nov. as type species, is described based on one female and four males in soil samples from India. The new genus is similar to the Neotropical genus Clausiadinychus Sellnick, 1930 (family Clausiadinychiidae Kontschán, Ermilov & Fridrich, 2023), but its gnathosomal appendages and the ventral setation are different from those of the new genus. The new genus resembles the Afrotopical genus Spinosissuropoda Hirschmann, 1979, but the new genus differs from the previously described one in the shape of idiosoma, dorsal setation, and anterior gnathosoma process.